TGF-β subverts the immune system into directly promoting tumor growth through IL-17 - Nam, Jeong-Seok (2008)
Overexpression of the immunosuppressive cytokine TGF-β is one strategy that tumors have evolved to evade effective immunesurveillance. Using transplantable models of breast and colon cancer, we made the unexpected finding that CD8+ cells in tumor-bearing animals can directly promote tumorigenesis, by a mechanism that is dependent on TGF-β. We showed that CD8+ splenocytes from tumor-bearing mice expressed elevated IL-17 when compared to naive mice, and that CD8+ T-cells could be induced to make IL-17 on addition of TGF-β and IL-6 in vitro. Treatment of mice with anti-TGF-β antibodies in vivo reduced IL-17 expression both in the tumor and the locoregional lymph nodes. Although IL-17 has not previously been shown to act as a survival factor for epithelial cells, we found that IL-17 suppressed apoptosis of several tumor cell lines in vitro, suggesting that this altered T-cell polarization has the potential to promote tumorigenesis directly, rather than indirectly through inflammatory sequelae. Consistent with this hypothesis, knockdown of the IL-17 receptor in 4T1 mouse mammary cancer cells enhanced apoptosis and decreased tumor growth in vivo. Thus, in addition to suppressing immune surveillance, tumor-induced TGF-β may actively subvert the CD8+ arm of the immune system into directly promoting tumor growth by an IL-17 dependent mechanism.